Collaborative Learning in ESP Speaking Classroom: Learners’ Perceptions and Experiences - Febrie Novitasari, N (KnE Social Sciences, 2019)
Collaborative learning approach has been widely used in classroom to improve the quality of learners’ learning process. This present study tried to assess twelve ESP learners’ perception and experiences with collaborative learning in their speaking class. The data were obtained by utilizing questionnaires and interviewing the learners. The findings revealed that most learners perceived collaborative learning positively. Collaborative learning effectively helped the learners learn in a comfortable environment. By implementing collaborative learning, the learners could work together to solve problems, to get meaningful feedbacks, and to trigger confidence which led to more opportunities to practice speaking. Keywords: collaborative learning, group discussion, ESP learners, speaking class